2022
DOI: 10.1108/ecam-12-2021-1105
|View full text |Cite
|
Sign up to set email alerts
|

Automatic generation of BIM-based construction schedule: combining an ontology constraint rule and a genetic algorithm

Abstract: PurposeThe purpose of this study is to automatically generate a construction schedule by extracting data from the BIM (Building Information Modeling) model and combining an ontology constraint rule and a genetic algorithm (GA).Design/methodology/approachThis study developed a feasible multi-phase framework to generate the construction schedule automatically through extracting information from the BIM, utilizing the ontology constraint rule to demonstrate the relationships between all the components and finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The results of this work are consistent with the research findings of [1][2][3][4], who stated that BIM technology and the REVIT software tool could minimize much of human errors and achieve a higher degree of precision. Also, these results are consistent with the findings of [5][6][7], who reported that the REVIT program could save considerable effort and time that would be significantly consumed by engineers to estimate the construction project cost. Also, the results of this study are compatible with [8][9][10], who analyzed the critical role of the BIM technology and REVIT software in estimating project costs and found that using the REVIT program can significantly cut effort, time, and cost required to calculate the construction projects costs that have higher complexity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this work are consistent with the research findings of [1][2][3][4], who stated that BIM technology and the REVIT software tool could minimize much of human errors and achieve a higher degree of precision. Also, these results are consistent with the findings of [5][6][7], who reported that the REVIT program could save considerable effort and time that would be significantly consumed by engineers to estimate the construction project cost. Also, the results of this study are compatible with [8][9][10], who analyzed the critical role of the BIM technology and REVIT software in estimating project costs and found that using the REVIT program can significantly cut effort, time, and cost required to calculate the construction projects costs that have higher complexity.…”
Section: Discussionsupporting
confidence: 90%
“…The construction projects' activities and parameters associated with each building task have been growing in the last decades, leading to higher challenges and difficulties for quantity surveyors to calculate the cost of each project as the complexity of these projects is remarkable. Additionally, if the calculation process relies on human efforts, the cost assessment will contribute to various errors and less precision, and it will consume much time [5][6][7]. In this context, designers, planners, and scholars have been working through decades of Research and Development (R&D) to develop BIM technology and REVIT software package that can be capable of providing state-of-the-art cost-evaluation techniques by which these problems can be alleviated and resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Topic 16- “Construction Project Management” concerns the research applying soft computing approaches in optimal planning of construction projects (Alotaibi et al ., 2022; Mahdavian and Shojaei, 2020), risk assessment (Elbashbishy et al ., 2022), optimizing the bidding decisions in projects (Mohamed et al ., 2022), construction process optimization (Shen et al ., 2022), cost prediction and optimization (Alsharqawi et al ., 2021; Sharma et al ., 2022a, b), construction schedule optimization (Wu and Ma, 2022), material procurement schedule optimization (Kar et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Construction Project Management • Analysing the implemented strategies by construction project decision-makers taken to establish the most costeffective renovation schedules that balance contractor profits and project expenses (AlOtaibi et al, 2022). • Explore the methods for optimizing the algorithm to better align with the needs of multi-objective equalization (Wu and Ma, 2022). Table 12.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used AI in coordination with 3D and 4D BIM to generate construction schedules [2,[13][14][15][16][17][18]. Kim et al [2] proposed a framework for automating schedule generation from BIM, where the sequencing rules are predefined.…”
Section: Previous Studiesmentioning
confidence: 99%